Newly Isolated Paenibacillus tyrfis sp. nov., from Malaysian Tropical Peat Swamp Soil with Broad Spectrum Antimicrobial Activity - Aw, Yoong-Kit; Ong, Kuan-Shion; Lee, Learn-Han; Cheow, Yuen-Lin; Yule, Catherine M.; Lee, Sui-Mae (Frontiers in Microbiology, 2016)
Emergence of antimicrobial resistance coupled with the slowdown in discovery of new antimicrobial compounds points to serious consequences in human health. Therefore, scientists are looking for new antimicrobial compounds from unique and understudied ecosystem such as tropical peat swamp forests. Over the course of isolating antimicrobial producing bacteria from North Selangor tropical peat swamp forest, Malaysia, a Gram variable, rod shaped, endospore forming, facultative anaerobic novel strain MSt1T that exerts potent and broad spectrum antimicrobial activity was isolated. Phylogenetic analysis using 16S rRNA gene sequences showed that strain MSt1T belonged to the genus Paenibacillus with the highest similarity with Paenibacillus elgii SD17T (99.5%). Whole genome comparison between strain MSt1T with its closely related species using average nucleotide identity (ANI) revealed that similarity between strain MSt1T with Paenibacillus elgii B69 (93.45%) and Paenibacillus ehimensis A2 (90.42%) was below the recommended threshold of 95%. Further analysis using in silico pairwise DDH also showed that similarity between strain MSt1T with P. elgii B69 (55.4%) and P. ehimensis A2 (43.7%) was below the recommended threshold of 70%. Strain MSt1T contained meso-diaminopilemic acid in the cell wall and MK-7 as the major menaquinone. The major fatty acids of strain MSt1T were anteiso-C15:0 (48.2%) and C16:0 (29.0%) whereas the polar lipid profile consisted of phosphatidylglycerol, phosphatidylethanolamine, diphosphatidylglycerol, one unknown lipid, two unknown glycolipids and one unknown phospholipid. Total DNA G+C content of strain MSt1T was 51.5 mol%. Extract from strain MSt1T exerted strong antimicrobial activity against Escherichia coli ATCC 25922 (MIC = 1.5 µg/mL), MRSA ATCC 700699 (MIC = 25 µg/mL) and Candida albicans IMR (MIC = 12.5 µg/mL). Partially purified active fraction exerted strong effect against Escherichia coli ATCC 25922 resulting in cell rupture when viewed with SEM. Based on distinctive taxonomic differences between strain MSt1T when compared to its closely related type species, we propose that strain MSt1T represents a novel species within the genus of Paenibacillus, for which the name Paenibacillus tyrfis sp. nov. (= DSM 100708T = MCCC 1K01247T) is proposed.